2010
DOI: 10.4314/ajfand.v10i10.62904
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of nutritional status of children in farming households in Oyo State, Nigeria

Abstract: This descriptive cross-sectional survey determined the influence of socioeconomic , household and child-related factors on the nutritional status of children (0-5yrs) in farming households of Oyo State, Nigeria. The study was conducted using a multistage sampling technique to select 201 mother-child pairs from 18 farming communities in the state. Data were collected from the mothers, using a structured interview schedule and anthropometric measurements of their children were taken to determine the prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 11 publications
2
24
2
1
Order By: Relevance
“…This depicts that the respondents are in their active years and are not likely to have challenges providing adequate nutrition for the child in their household. The findings from this study are consistent withLawal and Samuel (2010) who reported that the age of nursing mothers in the farming household in Oyo State was between 30 and 39 years. The majority (89.9%) of the respondents were married.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This depicts that the respondents are in their active years and are not likely to have challenges providing adequate nutrition for the child in their household. The findings from this study are consistent withLawal and Samuel (2010) who reported that the age of nursing mothers in the farming household in Oyo State was between 30 and 39 years. The majority (89.9%) of the respondents were married.…”
supporting
confidence: 92%
“…Despite several years of campaign for exclusive breast-feeding and complementary feeding, Udoh and Amodu (2016) stated that over 50% infants are given complementary foods before six months and the frequency of feeding for the child after six months is usually low, whereas the quantities and qualities of foods given are usually less than that required for the ages of the child. Although food has been described as the main source of good nutrition for all ages that supplies with substances that are referred to as nutrients (Meludu and Ajibade, 2009), households in rural areas appear to be food insecure and nutritionally vulnerable and undernourished compared to their urban counterparts (Lawal and Samuel, 2010), which most often reflects on the nutrition status of their children.…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Zambia showed no significant association between maternal education status and stunting and underweight whereas wasting prevalence did have a significant association with maternal education in which wasting prevalence were minimal in households with educated mothers [31]. On the other hand, a study done in Nigeria and Uganda showed that there was a positive association between levels of maternal education and nutritional indices [29, 32]. A study from Jimma in Ethiopia reported no statistically significant association between child nutritional status and education status [33].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, dietary inadequacy and lack of diversity constitute a common problem associated with low socioeconomic status, poor levels of education, lack of understanding of the role of food in health, and acute poverty [11]. This study examined the dietary adequacy and diversity of nutrients from diets consumed by farming households in Morogoro region, Tanzania.…”
Section: Introductionmentioning
confidence: 99%